Integration of Drone and GIS Data for Precision Land Use Mapping in Belayung Baru Village, Banjar Regency, South Kalimantan - Saputro, Maryam Eyka Dijono; Wijayanti, Fitri; Aditya, Haidar Fari; Chakim, M Ghufron (Journal of Applied Plant Technology, 2025)
The rapid advancement of remote sensing technology and Geographic Information Systems (GIS) has substantially enhanced the accuracy, efficiency, and comprehensiveness of spatial data acquisition and analysis. This study investigates land-use patterns within a selected area of Belayung Baru Village, Kertak Hanyar District, Banjar Regency, South Kalimantan, employing high-resolution drone imagery to generate detailed spatial information. A multirotor drone-based mapping survey was utilized, with data processed through Agisoft Metashape and ArcGIS to produce orthomosaic images and thematic land-use maps. The results reveal that the study area encompasses approximately 93.74 hectares, predominantly consisting of rice fields (65.86 ha), residential zones (17.15 ha), and wetlands (6.69 ha). Visual interpretation of drone imagery demonstrates pronounced seasonal contrasts between rice fields and wetlands in terms of spectral tone, texture, and spatial pattern. Furthermore, the dynamic hydrological conditions of the wetland ecosystem substantially influence local agricultural cycles, restricting cultivation to the dry season when the water table recedes. Overall, this study underscores the effectiveness of drone-based geospatial technology in delivering precise spatial mapping outputs that support sustainable land-use management and planning.